The ever‐increasing importance of cancer as a leading cause of premature death worldwide - Bray, Freddie; Laversanne, Mathieu; Weiderpass, Elisabete; Soerjomataram, Isabelle (Cancer, 2021)
The relative importance of cardiovascular disease (CVD) and cancer as leading causes of premature death are examined in this communication. CVD and cancer are now the leading causes in 127 countries, with CVD leading in 70 countries (including Brazil and India) and cancer leading in 57 countries (including China). Such observations can be seen as part of a late phase of an epidemiologic transition, taking place in the second half of the 20th century and the first half of the present one, in which the dominance of infectious diseases is progressively superseded by noncommunicable diseases. According to present ranks and recent trends, cancer may surpass CVD as the leading cause of premature death in most countries over the course of this century. Clearly, governments must factor in these transitions in developing cancer policies for the local disease profile. Cardiovascular disease and cancer are now the leading causes of premature death in the majority of countries worldwide, and cancer is likely to surpass cardiovascular disease as the leading causes of death at ages 30‐70 in most countries over the course of this century. Governments must factor in these transitions in formulating and implementing their cancer and noncommunicable disease plans and tailor cost‐effective measures to the local disease profile.